Novel finishing treatments of polyamide fabrics by electrofluidodynamic process to reduce microplastic release during washings. (July 2019) - De Falco, Francesca; Cocca, Mariacristina; Guarino, Vincenzo; Gentile, Gennaro; Ambrogi, Veronica; Ambrosio, Luigi; Avella, Maurizio
Abstract: Washing processes of synthetic clothes are considered the main source of microplastic pollution in the oceans, as during washing, microfibres are released and cannot be completely blocked by wastewater treatments plants, thus reaching the marine ecosystems. The development of mitigation approaches is strongly needed to prevent the impact of microplastics on marine environments. With the aim to protect the fabrics during the washing processes and then reduce the release of microfibres, in this work, new finishing treatments of polyamide fabrics were performed by an ElectroFluidoDynamic (EFD) method. This approach was used to obtain homogeneous coatings of biodegradable polymers, namely poly (lactic acid) and poly (butylene succinate- co -butylene adipate), on polyamide surface, without affecting the fabric hand and wettability. The treatments were very effective, able to significantly reduce the amount of microfibres released during washing tests, proving to be a promising application to mitigate microplastic pollution. Highlights: Thin and homogeneous coatings were obtained by an Electrofluidodynamic method. Biodegradable coatings were successfully applied on polyamide textile surface. The applied coatings unaltered the surface properties of polyamide fabric. The coatings were effective in reducing the release of microfibres during washing.